MATHEMATICAL MODELING OF THE MIXING PROCESS OF MULTI-COMPONENT FOOD MIXTURES IN THE VISIMIX PROGRAM - E. A. Timanovsky (Современная наука и инновации)
The mixing process is used in many areas of industry, such as food, chemical and oil refining, and its study is one of the most important tasks when modeling new mixing devices, as well as improving existing technologies.